Examining the Process of Life Skills Transfer from Sport to Life - Kendellen, Kelsey (Université d'Ottawa / University of Ottawa, 2019)
The purpose of this doctoral dissertation was to examine the life skills transfer process from sport to life. Data collection occurred over 10-months, from September 2016 to June 2017. The overall sample was comprised of 13 university intramural athletes and 29 social agents playing key roles in the athletes’ lives outside of sport (e.g., parents, partners, and work colleagues). Four methods of data collection were employed: (a) individual semi-structured interviews, (b) chronological charts, (c) timelines, and (d) solicited journals. The findings from this dissertation are organized into three articles. In article one, a grounded theory methodology was used to examine how athletes apply in life the skills they believe they learned or refined in sport. Within the substantive grounded theory, life skills application is framed as an ongoing process that involves four steps (a) decision-making, (b) application, (c) appraisal, and (d) adaptation. Article one adds to the literature by outlining the key behavioural and cognitive mechanisms that help explain what occurs once athletes move beyond sport and apply in different life domains the skills they deem to have learned or refined in sport. Article two presents a longitudinal integrated qualitative approach for “getting at” the life skills transfer process from sport to life. The integrated approach is illustrated through an exemplar case of a 23-year-old athlete (Claire) and her process of learning/refining emotional regulation in sport and applying this skill outside of sport. Three individuals able to speak to Claire’s behaviour outside of sport (i.e., mother, classmate, and work colleague) were also part of the case. Article two adds to the literature by demonstrating how qualitative techniques can be integrated to produce new insights on the life skills transfer process to an extent not previously gleaned through one-shot interview designs. In article three, the substantive grounded theory of life skills application was used to document one athlete’s (Joseph) journey through the life skills application process. Specifically, narrative inquiry was employed to tell Joseph’s story of applying the life skill of leadership at work as he progressed through the four steps described in the substantive grounded theory. Data collection involved three individual semi-structured interviews and three months of solicited journaling. Article three adds to the literature by moving beyond documenting examples of life skills application and instead, illustrating how Joseph’s emotions, thoughts, and behaviours evolved over time to influence his experiences of life skills application. Overall, the findings from this dissertation make theoretical, methodological, and empirical contributions to the life skills transfer literature in sport psychology and further elucidate the notion that sport can have a lasting impact on youth’s development.
Keywords: Sport Psychology; Life Skills; Sport; Youth Development; Transfer